Evaluation of the horizontal movement distance of elite female beach volleyball players during an official match - Hank, M.; Maly, T.; Zahalka, F.; Dragijsky, M.; Bujnovsky, D. (International Journal of Performance Analysis in Sport, 2016)
The purpose of this study was to evaluate distances and durations of horizontal movement of elite female beach volleyball players during matches. Four teams (n: 8; age: 28.6±5.8 years; height: 178.1±5.7 cm; body mass: 66.5±5.3 kg; mean±SD, respectively) were analysed by 3D kinematic analysis. 106 rallies (368 distances) were analysed. The average duration of a rally was 7.27±3.4 s. 83.7% of rallies lasted less than 10 s (63% lasted between 4 and 8 s and 27 % lasted longer than 8 s). The average distance of horizontal movement in all rallies was 9.39±5.67 m (in one set it was 287.5±19.7 m). 45.7% of measured distances ranged between 5 and 10 m. In total, 85.3% of distances measured less than 15 m, 14.7% measured more than 15 m. The field position of players (blockers and diggers) did not affect the covered distance during the game (t366 = 0.73, p = 0.47). Evaluation of player movement during performance is beneficial for assessing the crucial part of external workload and provides feedback in terms of tactical and conditional preparation. Results yielded information about external load and movements during the match.